Optimization of Solar Photovoltaic-Based Microgrid for Sustainable Energy Planning in Bajoe Port, Bone Regency, South Sulawesi: A Case Study - Mattuppuang, Andi Muhammad Hario; Gunawan, Gunawan; Utomo, Sukarno Budi (Library of Sultan Agung Islamic University, 2023)
Electrification in rural areas is still inadequate due to the limitations of the main power grid. Therefore, harnessing available renewable energy sources, such as solar energy, is an appropriate solution. The solar photovoltaic (PV) system can be utilized either in connection with the main power grid or in standalone mode (islanded) and can be supported by other power generation sources through a microgrid approach to enhance reliability. This research focuses on the design of a power system backed by a single renewable energy source, based on Photovoltaic (PV) technology, for the administrative building and passenger waiting area of Bajoe Port in Bone Regency. The microgrid technology is applied to improve the reliability and continuity of the electricity supply. The limited power supply at the site will be addressed using a microgrid system that combines power from the main grid, PV modules, and emergency generators. The system modeling takes into account the sensitivity of global climate conditions and local load requirements. The HOMER Pro software is utilized as a simulator to optimize the designed system. The PV module, with an array area of 186.92 m2, will be installed in the parking area of Bajoe Port, which covers an area of 3,264.3 m2. The best result for the PV system design within the microgrid system, with a capacity of 41.5 kWp, yields an electricity output of 180,451 kWh per year based on the local average solar irradiation of 5.05 kWh/m2/day. The economic evaluation, expressed in terms of Net Present Cost (NPC) amounts to Rp. 421,251,000, with a Cost of Energy (COE) of 126.04/kWh. Moreover, the system can contribute 110,305 kWh/year to the main grid operated by the state-owned utility, Perusahaan Listrik Negara (PLN). Simulation results indicate that the designed PV microgrid system can contribute to the local daily electrical load, with a daily power requirement of 117.78 kWh and excess energy being sold to the PLN grid.